The Standing Point of Ambalat Region for Indonesia Based on The United Nation Convention of The Law of The SEA 1982 Provisions - Prayudho Wicaksono; Rasji Rasji (Syntax Corporation, 2022)
Ambalat is a maritime region that falls under the jurisdiction of the State of Indonesia with an area of 4,735 square kilometers, located in the Sulawesi Sea or Makassar Strait and is near the extension of the land border between Sabah, Malaysia and East Kalimantan. With large oil and gas potential reserves of 764,000,000 barrels of oil and 1,400,000,000 cubic feet of gas. Therefore, the Ambalat Area is a strategic water region that is profitable for any country that controls the area, causing disputes over the ownership of the Ambalat Area between Indonesia and Malaysia. According to the provisions of United Nation Convention of The Law of The Sea 1982 (â€œUNCLOS 1982â€) especially at explanation in Article 47 paragraph (1) UNCLOS 1982, it is permissible to draw archipelagic baselines from the outermost point of an island is the right of the archipelagic state contained in Chapter IV UNCLOS 1982 concerning archipelagic states, as explained in Article 46 UNCLOS 1982. The archipelago block regime described in Article 47 UNCLOS 1982 does not apply to a coastal country. Therefore this journal spagel discuss about the provisions and regulation that stated on UNCLOS 1982 about the standing point of Ambalat region on UNCLOS perspective.